The Fiber-Optic Rotational Seismograph—Laboratory Tests and Field Application - Leszek R. Jaroszewicz; Anna Kurzych; Zbigniew Krajewski; Michał Dudek; Jerzy K. Kowalski; Krzysztof P. Teisseyre (Sensors, 2019)
The paper presents construction and laboratory tests, as well as the first field application of a new fiber-optic rotational seismograph. The system is based on a fiber-optic gyroscope (FOG), with determined Angle Random Walk of the order of 10−8 rad/Sqrt(s) and a few rad/s maximum detectable amplitude of rotation in the frequency range from direct current (DC) to 328.12 Hz. It has been designed for the rotational seismology area of interest. This work also presents exemplary relevant measurements, which were conducted using a set of two devices installed in the geophysical observatory in Książ, Poland.